Unravelling the transcriptomic dynamics of Hyphopichia pseudoburtonii in co-culture with Botrytis cinerea. - Evelyn Maluleke; Neil Paul Jolly; Hugh-George Patterton; Mathabatha Evodia Setati (PLoS ONE)
Hyphopichia pseudoburtonii, is emerging as a potential biocontrol agent against various phytopathogens. These traits have been attributed to the production of various antifungal compounds in the presence of target pathogens. However, the broad molecular mechanisms involved in the antifungal activity are not yet understood. This study employed RNA sequencing to assess the temporal changes in H. pseudoburtonii Y963 gene expression patterns when co-cultivated with Botrytis cinerea. Genes differentially expressed in H. pseudoburtonii in co-culture with B. cinerea, compared to the monoculture were evaluated after 24, 48, and 120 h of growth. Up-regulation of genes encoding major core histones (H2A, H3, H4) and ribosomes in the first 24 h suggested an abundance of cells in the S phase of the cell cycle. At 48 h, the genes up-regulated highlight mitotic cell cycle activity and induction of filamentous growth, while in later stages, up-regulation of genes encoding high affinity transporters of sugars, copper and iron, as well as those involved in the retention and utilization of siderophore-iron was evident. Altogether, the data allude to competition for space and nutrients as key mechanisms activated in H. pseudoburtonii in the presence of B. cinerea. This research offers new insights into H. pseudoburtonii transcriptomic response to B. cinerea and illuminates the adaptive strategies and molecular mechanisms behind its antifungal activity.